Effect of Cissus quadrangularis Linn on skeletal growth in the neonates of diabetic rats - Sirasanagandla, Srinivasa Rao; Pai, K. Sreedhara Ranganath; Bhat, Kumar M. R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Infants of the diabetic mother are known to have reduced bone mineral content and hypocalcemia. Earlier, it has been shown that petroleum ether extract of Cissus quadrangularis (PECQ) can enhance the fetal skeletal ossification in normal rats. The present study was designed to evaluate the effect of PECQ on skeletal growth in the neonatal rats of streptozotocin-induced diabetic rats. Methods: After confirmation of diabetes, the diabetic and non-diabetic female Wistar rats were kept for mating with healthy male rats. After positive vaginal smear test, the pregnant rats were divided into three groups; the normal (non-diabetic) control (NC), diabetic control (DC), and diabetic+CQ (D+CQ) groups. The rats in the D+CQ group were given PECQ (500 mg/kg B.Wt), whereas animals in NC and DC groups were given 0.5% carboxy methyl cellulose, throughout the gestational period. Femur from the 1 week old neonatal rats from each group was collected randomly and subjected to histological analysis. Results: Thickness of trabecular bone and periosteum was significantly reduced in the neonates of DC rats compared with the neonates of NC group. Pretreatment with PECQ significantly improved the thickness of trabecular bone and periosteum compared with neonatal rats of DC group. No significant differences were observed in the medullary cavity width of femur between the groups. Conclusion: Data from the present study suggest that the PECQ can effectively attenuate the diabetes-induced reduction in the early skeletal growth. However, further research is warranted to evaluate the exact mechanism of action of phytochemical constituents of PECQ that can cross the placental barrier.